2012
DOI: 10.1603/ec11243
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Potential of Natural Zeolite and Diatomaceous Earth Formulations Against Rice Weevil (Coleoptera: Curculionidae) and Red Flour Beetle (Coleoptera: Tenebrionidae)

Abstract: Insecticidal potential of natural zeolites and diatomaceous earths originating from Serbia against Sitophilus oryzae (L.) and Tribolium castaneum (Herbst) was evaluated. Two natural zeolite formulations (NZ and NZ Modified) were applied to wheat at rates of 0.50, 0.75, and 1.0 g/kg, while two diatomaceous earth (DE) formulations (DE S-1 and DE S-2) were applied at rates of 0.25, 0.50, 0.75, and 1.0 g/kg. A bioassay was conducted under laboratory conditions: temperature of 24 +/- 1 degrees C, relative humidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Inert dusts, such as zeolite, are promising alternative to conventional chemical insecticides and have been extensively researched and used in practice due to their low mammalian toxicity and slight or no effect on quality products treated with commercially applicable concentrations (Korunic 1998;Andric et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Inert dusts, such as zeolite, are promising alternative to conventional chemical insecticides and have been extensively researched and used in practice due to their low mammalian toxicity and slight or no effect on quality products treated with commercially applicable concentrations (Korunic 1998;Andric et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bentonite (Bosnia and Herzegovina), natural zeolite (Serbia) and DE (Belgrade, Serbia) formulations were found, under laboratory conditions, to be effective against S. oryzae and T. castaneum adults . Zeolites and modified zeolits originating from Serbia were also studied to test progeny reduction rates and the insecticidal effect of stored product insects, with good results being reported …”
Section: Application Of Insecticide and Herbicide Carriers And Pestimentioning
confidence: 99%
“…41 Zeolites and modified zeolits originating from Serbia were also studied to test progeny reduction rates and the insecticidal effect of stored product insects, with good results being reported. 50 South American native flowering plants that release peppery odor 'Matico' (Piper aduncum subsp. ossanum) as PAO-1, PAO-2 and zeolite (Heulandite type Zeolite which Clinoptilolite + Mordenite Type I, purity is above 70%) were studied to control the cigarette beetle, Lasioderma serricorne (F.) (Coleoptera: Anobiidae) in chickpea, showing the highest mortality rates of adults with PAO-2 and the best repellent effect with PAO-1.…”
Section: Application Of Insecticide and Herbicide Carriers And Pestimentioning
confidence: 99%
“…Increasing evidence has highlighted the potential use of DE for insect control (1921). Recent studies have demonstrated the insecticidal effect of DE against different species of mites in animal (10, 22).…”
Section: Discussionmentioning
confidence: 99%